Adherence to postresection colorectal cancer surveillance at National Cancer Institute‐designated Comprehensive Cancer Centers. (18th October 2018) - Kupfer, Sonia S.; Lubner, Sam; Coronel, Emmanuel; Pickhardt, Perry J.; Tipping, Matthew; Graffy, Peter; Keenan, Eileen; Ross, Eric; Li, Tianyu; Weinberg, David S.
Abstract: Guidelines recommend surveillance after resection of colorectal cancer (CRC), but rates of adherence to surveillance are variable and have not been studied at National Cancer Institute (NCI)‐designated Comprehensive Cancer Centers. The aim of this study was to determine rates of adherence to standard postresection CRC surveillance recommendations including physician visits, carcinoembryonic antigen (CEA), computed tomography (CT), and colonoscopy after CRC resection at three NCI‐designated centers. Data on patients with resected CRC from 2010 to 2017 were reviewed. Adherence to physician visits was defined as having at least two visits within 14 months after surgical resection. CEA adherence was defined as having at least four CEA levels drawn within 14 months. CT and colonoscopy adherence were defined as completing each between 10 and 14 months from surgical resection. Chi‐square test and logistic regression analyses were performed for overall adherence and adherence to individual components. A total of 241 CRC patients were included. Overall adherence was 23%. While adherence to physician visits was over 98%, adherence to CEA levels, CT, and colonoscopy were each less than 50%. Center was an independent predictor of adherence to CEA, CT, and/or colonoscopy. Stage III disease predicted CT adherence, while distance traveled of 40 miles or less predicted colonoscopy adherence. Overall adherence to postresection CRC guideline‐recommended care is low at NCI‐designated centers. Adherence rates to surveillance vary by center, stage, and distance traveled for care. Understanding factors associated with adherence is critical to ensure CRC patients benefit from postresection surveillance. Abstract : Guidelines recommend surveillance after resection of colorectal cancer, but rates of adherence are variable and have not been studied at NCI‐designated comprehensive cancer center. Our study found low overall adherence that varied by center, stage, and distance traveled for care.